DEVELOPMENT OF WEB DASHBOARD FOR VISUALIZING MACHINE LEARNING-BASED BEAM TRACKING ON 5G HIGH SPEED TRAIN - Tinarta, David
At the command center of PT Kereta Api Indonesia, high-capacity services are required to ensure smooth and efficient operations. The performance of beam tracking on the 5G network is crucial to monitor in order to maintain optimal service quality. Therefore, a dashboard capable of visualizing beam tracking performance data is needed to allow operators to monitor and assess network performance. This way, potential issues can be identified and addressed to reduce the risk of service disruptions. Additionally, the dashboard is expected to assist in analyzing historical data to evaluate long-term performance and make decisions based on observed trends. The ability to customize the data display according to needs also allows operators to focus on the metrics and parameters most relevant